Mekanisme Pasar Dalam Perspektif Ekonomi Islam - Yenni Samri Juliati Nasution (Universitas Islam Negeri Sumatera Utara, 2018)
The market is a mechanism for the exchange of goods and services that nature. The market price is formed by a variety of factors which later formed the demand and supply of goods and services. Consumer demand is influenced by many factors, such as price, consumer income, tastes, expectations and level mashlahah. Quote manufacturers also influenced by many factors, such as mashlahah, profits, and prices. Interaction of supply and demand will establish the balance point can be changed from the demand side or the supply, either due to the deviation of structured and unstructured deviation. Perfectly competitive market can generate a fair price for the seller and the buyer. Therefore, if the market mechanism is interrupted, then the fair price will not be achieved. Islam puts the market at an important position in the economy. And very concerned about the concept of a fair price and perfect market mechanism. So, the role of government is very important to better ensure the activities of market mechanisms as perfect as taking a policy of price intervention that is based on justice.